1992
DOI: 10.1007/bf00310024
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical demonstration of interphotoreceptor retinoid-binding protein in cerebellar medulloblastoma

Abstract: Previously, immunoreactive rod-opsin and S-antigen (arrestin), two highly characteristic markers of retinal photoreceptors and pinealocytes, were shown to be present in certain medulloblastoma cells. It, thus, has been suggested that such cells differentiate along the photoreceptor lineage. This is corroborated in the present immunocytochemical investigation using antibodies against another photoreceptor-cell marker, the interphotoreceptor retinoid-binding protein (IRBP). As shown in preparations of human reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Interestingly, these retina-associated substances have not been demonstrated in neuroblastoma and ganglioneuroblastoma, tumors often "lumped" into the PNET category. 46 To date, one small study of medulloblastomas has demonstrated no alterations of the retinoblastoma susceptibility gene. 48 Cytogenetic and molecular genetic studies of PNET and PPT have shown more differences than similarities.…”
Section: Relation Of Pineal Parenchymal Tumors To Pnetmentioning
confidence: 99%
“…Interestingly, these retina-associated substances have not been demonstrated in neuroblastoma and ganglioneuroblastoma, tumors often "lumped" into the PNET category. 46 To date, one small study of medulloblastomas has demonstrated no alterations of the retinoblastoma susceptibility gene. 48 Cytogenetic and molecular genetic studies of PNET and PPT have shown more differences than similarities.…”
Section: Relation Of Pineal Parenchymal Tumors To Pnetmentioning
confidence: 99%
“…For instance, Huang, Klein, and Korf (1992) described expression of rod opsin in a small fraction of adult human pinealocytes. Expression of S-arrestin (Perentes, Rubinstein, Herman, & Donoso, 1986) and recoverin (Korf, Korf, Schachenmayr, Chader, & Wiggert, 1992) was also described. The significance of these observations remains unknown.…”
Section: Cellular Composition Of the Pineal Glandmentioning
confidence: 99%
“…Interphotoreceptor retinoid-binding protein (IRBP) is a glycoprotein with a molecular mass of 145 kDa and is expressed by retinal photoreceptors 1 2. It is thought to mediate the transport of retinoids between the retinal photoreceptor cells and the RPE 1 2.…”
Section: Answersmentioning
confidence: 99%
“…It is thought to mediate the transport of retinoids between the retinal photoreceptor cells and the RPE 1 2. IRBP has been widely used for induction of experimental autoimmune uveitis 2.…”
Section: Answersmentioning
confidence: 99%
See 1 more Smart Citation